Building health: Motivational factors to enhance systematic work environment management in the construction industry - Niklas Rydbo; Kristina Aurelius; Martin Grill; Christian Jacobsson; Anders Pousette (PLoS ONE, 2025)
Objective The aim of the study was to investigate whether and how the interventions have been beneficial in developing a well-functioning systematic OSH management. The aim was also to investigate whether and how the interventions have facilitated or impeded autonomous motivation to develop a well-functioning systematic OSH management. Method Data were collected through individual interviews with participants in the Health Construction intervention project and audio recordings from the concluding workshop for each batch. The data were analyzed using an inductive thematic analysis. Results The seven themes from the analysis yielded the following results. Participation in the project was highlighted as a key factor for development, as it offered opportunities to collaborate and share experiences and insights about the domain of the occupational environment with representatives from other companies. Establishing a development team within participating companies appears to have influenced the legitimacy of occupational safety and health, as well as the assigned safety priority. A process consultative approach by external consultants seems to have contributed to an enhanced ability to articulate thoughts, identify solutions, synthesize discussions, and work effectively within the development team. The results suggest that the assigned safety priority of the respective participating companies has increased. Additionally, there are indications that autonomous motivation to continue and deepen efforts to address safety and health issues in a structured way has increased within the participating companies. Conclusions The results of this study indicate that the interventions implemented in the project have been beneficial in fostering the development of a well-functioning systematic occupational safety and health management. This may have been achieved by enhancing the autonomous motivation to prioritize and develop a healthy and safe work environment within the participating companies.